Antidiuretic and antidiarrhoeal activities of polar and non-polar extract of Brassica oleracea - Abu Afzal Mohammad Shakar, Sharmin Khanam, Muhammad Shahdaat Bin Sayeed, Md. Ahsanul Haque, Md. Moniruzzaman, S.M. Ashraful Islam (Journal of Applied Pharmaceutical Science)
Diuretic activities of both polar and non-polar extract of leaves of Brassica oleracea were investigated on male white rabbits and male Sprague-Dawley rats. Anti diarrheal activity of the same extract was investigated on male and female swiss albino mice. Both polar and non-polar extract exhibited anti diuretic activities on both rats and rabbits. Polar and Non-polar extract also showed anti diarrheal activity on male and female mice. Anti diarrheal activity affects both latent period and number of stools.
Keywords: Brassica oleracea,Anti diuretic,Anti diarrheal activity,Polar extract,Non-polar extract.